Law Enforcement Against Minors Committing Traffic Violations Within the Jurisdiction of the Simalungun Resort Police - Fadhillah, Haris; Rafianti, Fitri; Aspan, Henry (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze law enforcement regarding traffic violations committed by minors within the jurisdiction of the Simalungun Resort Police (Polres Simalungun) and to identify the obstacles involved in such enforcement. The research employs an empirical juridical method (socio-legal research) utilizing statutory, conceptual, and case-based approaches, with data analyzed through a descriptive-qualitative method. The findings indicate that traffic violations by minors are frequently encountered within the Simalungun Resort Police’s jurisdiction. The police employ a multi-faceted strategy to address these violations: preemptive measures involving public awareness campaigns and guidance sessions at schools—engaging teachers, parents, and community leaders; preventive measures such as patrols and traffic management near schools; and repressive measures involving enforcement operations and the penalizing of violators. Despite these efforts, traffic violations remain common, driven by factors such as limited public transportation in certain areas, significant distances between homes and schools, and the freedom parents grant their children. The study concludes that preventing traffic violations by minors requires the active participation of parents and teachers, local government support in providing and facilitating transportation facilities in specific areas, and firm law enforcement.